An overview of structural aspects and health beneficial effects of antioxidant oligosaccharides - Vieira, Tatiane F. (2018)
Background: Non-digestible oligosaccharides are versatile sources of chemical diversity, well known for their prebiotic actions, found naturally in plants or produced by chemical or enzymatic synthesis or by hydrolysis of polysaccharides. Compared to polyphenols or even polysaccharides, the antioxidant potential of oligosaccharides is still unexplored. The aim of the present work was to provide an up-to-date, broad and critical contribution on the topic of antioxidant oligosaccharides. Methods: The search was performed by crossing the words oligosaccharides and antioxidant. Whenever possible, attempts at establishing correlations between chemical structure and antioxidant activity were undertaken. Results: The most representative in vitro and in vivo studies were compiled in two tables. Chitooligosaccharides and xylooligosaccharides and their derivatives were the most studied up to now. The antioxidant activities of oligosaccharides depend on the degree of polymerization and the method used for depolymerization. Other factors influencing the antioxidant strength are solubility, monosaccharide composition, the type of glycosidic linkages of the side chains, molecular weight, reducing sugar content, the presence of phenolic groups such as ferulic acid, and the presence of uronic acid, among others. Modification of the antioxidant capacity of oligosaccharides has been achieved by adding diverse organic groups to their structures, thus increasing also the spectrum of potentially useful molecules. Conclusion: A great amount of high-quality evidence has been accumulating during the last decade in support of a meaningful antioxidant activity of oligosaccharides and derivatives. Ingestion of antioxidant oligosaccharides can be visualized as beneficial to human and animal health.